The Effect Of Capital Intensity, Leverage, Profitability, And Firm Size On Tax Aggressivity - Noviyanti, Diah Ayu; Kartika, Andi; Ma'sum, Muhammad Ali (Pusat P2M Politeknik Negeri Batam, 2024)
This study aims to examine the effect of Capital Intensity, Leverage, Profitability, and Company Size on Tax Aggressiveness. This study uses multiple linear regression analysis with the SPSS (Statistical Package for Social Sciencess) program. The population in this study were food and beverage companies listed on the Indonesia Stock Exchange during the observation period 2017-2022. The sampling technique used in this study was purposive sampling method, which is a sampling technique based on criteria determined by the researcher. Based on the sample selection criteria, 48 research data were obtained. The results of this study indicate that: (1) Capital Intensity has a positive and significant effect on Tax Aggressiveness; (2) Leverage has no effect on Tax Aggressiveness; (3) Profitability has no effect on Tax Aggressiveness; (4) Company Size has a positive and significant effect on Tax Aggressiveness.